PENERAPAN TEKNOLOGI QR CODE DAN APLIKASI MOBILE SEDERHANA UNTUK DIGITALISASI KEHADIRAN SERTA DETEKSI DINI STATUS GIZI BALITA DI POSYANDU - Susana Dwi Yulianti; Hermawan, Indra; Widya Iswara, Ratna; Eka Miharja, Mochamad; Rauf, Faisal (Jurnal Pepadu, 2025)
Posyandu (integrated health service post) plays a vital role in monitoring child growth and early detection of nutritional problems. However, manual recording methods that are still widely used often result in errors, delays in reporting, and difficulties in accessing data. This community service program aims to improve efficiency and accuracy in data recording through the implementation of a digital system based on QR Code technology and a simple mobile application at Posyandu Orchid, Sawangan, Depok. The program was carried out using a Participatory Action Research (PAR) approach, involving Posyandu cadres in all stages, including problem identification, system design, training, implementation, monitoring, and evaluation. The results show that the developed digital system successfully replaces manual recording, speeds up the attendance process for toddlers, and facilitates nutritional status reporting. Furthermore, the program has enhanced the digital literacy of Posyandu cadres and increased parental awareness of the importance of nutritional monitoring. The application of this technology has proven effective in supporting the digital transformation of community-level health services and can be replicated in other Posyandu